2022
DOI: 10.3390/diagnostics12112757
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index, Controlling Nutritional Status (CONUT) Score, and Inflammatory Biomarkers as Predictors of Deep Vein Thrombosis, Acute Pulmonary Embolism, and Mortality in COVID-19 Patients

Abstract: Background: Numerous tools, including nutritional and inflammatory markers, have been evaluated as the predictors of poor outcomes in COVID-19 patients. This study aims to verify the predictive role of the prognostic nutritional index (PNI), CONUT Score, and inflammatory markers (monocyte to lymphocyte ratio (MLR), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), systemic inflammatory index (SII), Systemic Inflammation Response Index (SIRI), and Aggregate Index of Systemic Inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 69 publications
3
55
2
Order By: Relevance
“…A low PNI means that patients have a poor immune and nutritional status, which may be related to the poor prognosis of tumor patients [ 12 , 13 , 14 , 15 , 28 ]. Meanwhile, the PNI has also been confirmed to be associated with the development and progression of multiple chronic diseases [ 29 , 30 , 31 ]. Several studies confirmed that the PNI is also closely related to the prognosis of HCC patients [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A low PNI means that patients have a poor immune and nutritional status, which may be related to the poor prognosis of tumor patients [ 12 , 13 , 14 , 15 , 28 ]. Meanwhile, the PNI has also been confirmed to be associated with the development and progression of multiple chronic diseases [ 29 , 30 , 31 ]. Several studies confirmed that the PNI is also closely related to the prognosis of HCC patients [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Halmaciu et al published an article in which they proved the prognostic impact of NLR > 6.97 and MLR > 0.54 in COVID-19 patients' death ( 29 ). Muresan et al concluded that NLR > 9.4 and MLR > 0.78 are associated with mortality in a study conducted in a group of 889 patients with COVID-19 ( 30 ). From the above research results, NLR and MLR can well-reflect the occurrence and development of many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are also robust data reporting the predictive powers of NLR and PLR for numerous COVID-19-related outcomes in critically ill patients. Studies on similar demographics have reported good predictive value for NLR and PLR regarding the occurrence of deep vein thrombosis, acute pulmonary embolism, acute limb ischemia, need for invasive mechanical ventilation, ICU admission and mortality [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%